The Effectiveness of Ethnopedagogy Based Problem Based Learning Model on Students' Digital Literacy - David Marthen Salakory (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research is to determine the effectiveness of the ethnopedagogy-based problem based learning model on students' digital literacy. The type of research is meta-analysis research. The data sources in the research come from 13 national and international journals published from 2021-2024. Search for data sources through the online databases Google Scholar, ScienceDirect, Wiley and Researchgate. Data collection techniques are direct observation and documentation. Inclusion criteria are research originating from journals and proceedings indexed by Sinta, Scopus, EBSCO, Copernicus International and IEEE, research related to ethnopedagogy-based project based learning models for students' digital literacy, research having complete data to calculate the effect size, research must be open access, and has a sample size of 25 students. Data analysis through quantitative analysis by calculating the effect size value of each study with the help of the JSAP application. The research results concluded that the problem based learning model based on ethnopedagogy had a significant influence on digital literacy with an average effect size value of 0.819 with high effect size criteria. These findings provide important information for teachers in implementing problem based learning based on student ethnopedagogy to develop digital literacy.